Strategy : - Thompson, Jr. Arthur A. (McGraw-Hill, 2006)
"Strategy: Winning in the Marketplace" is the newest offering from proven authors Thompson, Gamble, and Strickland. As in previous works, the authors' mainstream presentation includes the most recent research in strategy presented in a way that students can understand and apply to business cases and problems. With fewer chapters and pages than previous texts by these authors, this text offers a more concise, lively, and user-friendly presentation of strategic management. Fundamental strengths of Thompson/Gamble/Strickland text treatments are very much evident in this edition - a compelling presentation of Porter's Five-Forces model and globally competitive markets and first-rate coverage of strategy execution and the drive for operating excellence.